A Critical Digital Plan on How to Control Fake News in Nigeria - NNABUIFE, Sheila; Jarrar, Yosra (Dirasat: Human and Social Sciences, 2019)
The rate at which fake news thrive in the social media landscape around the world has attracted media scholars attention in different ways given the threat and dangers it poses to the peaceful development of every human society. In view of the above reason, this study is set to provide critical digital measure that can help the government of Nigeria in the control of fake news spread in its territory considering the heterogeneous nature of the country. The study is set to find out if there is any noticeable influence of fake news on the existence of the Nigerian state, the dominant noticeable dangers of fake news, and the various available digital measures that can control it and to provide a sound record keeping digital regulation to identify all individual social media users. The study is premised on the theory of reasoned action and planned behavior and the source credibility theory. The study adopts the online survey research method in studying 253 media scholars - all members of ACCE Whatsapp group. Findings revealed that fake news threatens the unity of Nigeria and that those who post, read, accept and share fake news online do that as a planned motif which can be religiously, politically or economically motivated. The study therefore recommends that social media users should at always be skeptical about what to read, accept and disseminate to the public and that An International Fact Checking Network (IFCN), should be used in regulating social media contents.